Inhibition of the Plasma-Membrane-Associated Serine Protease Cathepsin G by Mycobacterium tuberculosis Rv3364c Suppresses Caspase-1 and Pyroptosis in Macrophages - Danelishvili, Lia; Everman, Jamie; McNamara, Michael; Bermudez, Luiz (Frontiers in Microbiology, 2012)
Tuberculosis is a disease associated with the infection of a great part of the world’s population and is responsible for the death of two to three million people annually. Mycobacterium tuberculosis infects macrophages and subverts its mechanisms of killing. The pathogen suppresses macrophage apoptosis by many different mechanisms. We describe that, upon uptake by macrophages, M. tuberculosis overexpresses an operon Rv3361c – Rv3365c and secretes Rv3364c. The Rv3365c knockout strain is deficient in apoptosis inhibition. The Rv3364c protein binds to the serine protease cathepsin G on the membrane, inhibiting its enzymatic activity and the downstream activation of caspase-1 dependent apoptosis. In summary, M. tuberculosis prevents macrophage pyroptosis by a novel mechanism involving cytoplasmic surveillance proteins.